When visual practices became mediatized: the context of the signification mode of Modernism and the Classic culture industry - Pavlova, Olena (Ukrainian Cultural Studies, 2022)
Visual practices (the dominance of sight through appealing to it the signifier order of the the carrier, but not the complete absence of other sensory orientations) were mediatized, that was, they formed mass audiences (both in participants numbers and the most dense form of integration into society as a whole). This was not possible without cultural technologies covering the everyday level of interaction between people and things, institutes as well as culture became ordinary. Another attribute of media functioning was mass attractiveness (pleasure of the media (e.g. text), not of the artistic work), i.e. realization as a form of "meaning culture" (H.  Gumbrecht's term, i.e. beyond the motivation of lack or coercion). The attractiveness of visual media is one of forms of the image practices (G.  Boehm 's term, but not of the artistic image and not of the picture contemplation). Thus, mediatization became possible in the process of culture industrialization (i.e. industrial production makes possible both surplus and excess), in particular as the form of "classic culture industry" (S. Lash). It was formed against the background of penetration of inventions of the second industrial revolution into communication technologies. On the other hand, the media in the "The long nineteenth century" (E. Hobsbawm) are predominantly visual because the dominant forms of sensory orientation are based on technologies and cultural products whose signifiers order appealed to the eye (press, photography, silent cinema). Therefore, the way of signification of modernism (blurring the connection with the referent by the play intensifying of the signifier and the signified) was carried out mainly in the logic of mediatization of visual practices through both industrial replication of signifiers and diversification of the orders of the latter (the premise of signifieds multiplicity). A derivative of industrialization and mediatization (de-differentiation with technical carriers, mass audience and attractiveness of the cultural product for it, its ordinary) of culture was the requirement of its newsworthiness (endless updating of media content as a necessary component of the signifiers diversity, a of the dominance rate of the meaning culture). Other forms of mediatization (museums, cafes, cabarets, concerts, music production, etc.) are derived from hybridization with visual media (representation in the press and photographs, film news is an indispensable element of commercial success), as well as spectacularity as a necessary parameter of any media. Mediatization and visualization as a factor in the modernism mod and the classic culture industry caused a powerful transformation of the humanities, in particular the emergence of the fields of cultural history (the reception of the rewriting of the past by the present) and the phenomenology of perception (the rehabilitation of the integrity of sensory orientations beyond their reduction to sight).Mediatization of visual practices in the logic of the formation of the classic culture industry contained the following elements of implementation: mechanization of production and reproduction of cultural products, accordingly, its reduction in price and the possibility of being commercialized, mass consumption, and, consequently, production, of a mass audience. The signification mod of modernism includes "the desacralization of the image of the Author" (scriptwriter, not creator; collective, not person, individual) and the disappearance of the aura of the artistic work (the order of signifiers becomes derived from technical parameters, and therefore, the media become actors of cultural production).
Keywords: visual media; visual practices; contemplation; spectacle; high culture; classic culture industry; optical mediа